Navigating the European Migration Regime Male Migrants, Interrupted Journeys and Precarious Lives - Wyss, Anna (Global Migration and Social Change, 2022)
EPDF and EPUB available Open Access under CC-BY-NC- ND Anna Wyss' survey of the heavily politicised group of male migrants in Europe provides insightful analysis of both masculinity and the European migration crisis. The book tracks men's repeated attempts to achieve permanent residence status and the successive detentions and deportations they endure. It measures the effects of precarity on their lives and explores the hope and vulnerability they experience.